The best course available : a personal account of the secret U.S.-Japan Okinawa reversion negotiations - Wakaizumi, Kei, 1930-1996.; Nilsson-Wright, John. ([Honolulu] : University of Hawai'i Press, 2002)
"This volume affords a look at the sensitive issue of nuclear diplomacy between two critical Cold War allies, the United States and Japan, during the 1960s.
Challenging the silence of the official bureaucracies in Washington and Tokyo, Wakaizumi Kei reveals the truth behind the secret 1969 agreement that ensured the eventual reversion of Okinawa to Japanese jurisdiction in 1972. Revelation of this sec.
With the publication of this translation, his description of the events leading up to the closed-door agreement is available to an English-language audience for the first time."--Jacket
Chapter 9 Top Secret Negotiations at the White HouseChapter 10 Writing the Script in Collaboration with Henry Kissinger; Chapter 11 A Nuclear- Free, Homeland- Level Reversion by 1972; Chapter 12 The Textiles Question; Chapter 13 All I Can Do Is Await the Judgment of Future Historians -- Chapter 14 In the Dark Recesses of History; Afterword; Notes; Index.
"In association with Program on Education and Training, East-West Center."
Includes bibliographical references (pages 337-359) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: United States -- Foreign relations -- Japan; Japan -- Foreign relations -- United States; United States -- Foreign relations -- 1945-1989.; Japan -- Foreign relations -- 1945-1989.; Okinawa Island (Japan) -- History -- 20th century; Japon -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- 1945-1989.; Japon -- Relations extérieures -- 1945-1989.; Okinawa (Japon : Île) -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Japan; Japan -- Okinawa Island; United States; Onderhandelingen; Okinawa; 1900-1999; History